Necessities of employee productivity in garment industries: Challenges and effects of harassment, abuse and discrimination - Alam M.N.; Bahar A.K.M.M.; Jambulingam M.; Hassan M.D.M. (Inderscience Publishers, 2023)
Harassment and discrimination are the common phenomena in human resource practices in the ready-made garments (RMG) industry. At the context of the research, in the Bangladeshi RMG industry, employees' productivity became lowest compared to her competitors like China, India, Pakistan, Sri Lanka, Cambodia. This RMG industry of Bangladesh would be a challenge to survive in the world market unless they improve employee productivity. Therefore, the primary purpose of this research was to observe the relationship between harassment and abuse, discrimination, and employee productivity with the view of employee work motivation as a mediator. The study was conducted under the positivism philosophy, a deductive approach, explanatory research design, quantitative methodology, and cross-sectional data were used. In a questionnaire survey, 25 items were taken from existing literature to measure the variables. By a systematic probability sampling technique, 500 viable samples were collected from the population for generalising the study. SPSS and smart-PLS were used for analysing and developing the model. However, the results revealed that all seven hypotheses were supported. These findings will help the policymakers, the government, factory owners, managers, and other stakeholders to formulate the policy and practice. Future research directives were also derived from this study. 2021 Inderscience Enterprises Ltd.